Visualising penetration in armour - Powell, Daniel (Cranfield University, 2022)
The human eye, CT scanning, X-ray radiography and Computer Aided Design (CAD) can all be used to visualise penetration in armour systems. This digital image demonstrates how these advanced techniques help us see a story that often seems non-existent to the human eye. X-ray radiography in the x and y axis paired with subsequent computer modelling allows the recreation of the crater and embedded material in 3D, enabling detailed analysis of the armour penetration. The volume of penetration can be measured with 95% accuracy from this CAD model when compared to the more expensive and complex, yet highly accurate, CT scanning. This demonstrates the reliability of this relatively simple and accessible methodology for quantifying damage in armour systems.
Keywords: Ceramic armour'; 'Impedance'; 'Penetration'; 'DSDS21'; 'DSDS21 Digital Image'; 'Defence Studies'